Pengaruh E-Promotion, Harga, Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Lokal Somethinc Di Official Store (Studi Pada Mahasiswi Kampus Di Kota Malang) - Oktorica, Lidya Dwi; Wahono, Budi; Rachmadi, Kartika Rose (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to analyze the effect of e-promotion, price, and product quality on purchasing decisions for the Somethinc local brand, both simultaneously and partially. The population in this study were female students studying at a university in Malang City. The sample of this study were 80 female students studying at a university in Malang City , who had purchased Somethinc products from the official marketplace store. Quantitative methods with a survey approach and distributing questionnaires were used. The results of multiple linear regression analysis show that e-promotion, price, and product quality simultaneously have a significant effect on purchasing decisions. Partially, each variable also has a significant effect on purchasing decisions. This study suggests that businesses focus on attractive e-promotion strategies, affordable prices, and maintaining product quality to increase consumer loyalty. Keywords: E-Promotion, Price, Product Quality, and Purchase Decision.